2014
DOI: 10.1111/1467-954x.12127
|View full text |Cite
|
Sign up to set email alerts
|

Technologies of Recovery: Plans, Practices and Entangled Politics in Disaster

Abstract: Recovery practices following the loss of home, sense of security, space and possessions, have recently become a focus of UK government attention. How people recover from disasters is seen to have a direct bearing on individual, community and economic well-being, so that the recovery itself becomes a form of social change. A plethora of instruments: templates, checklists and guidance documents have been produced to effect this recovery. We term these 'technologies of recovery', which work within a wider context… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 11 publications
(13 reference statements)
0
14
0
Order By: Relevance
“…Detailed, ethnographic, policy-specific studies have characterised contemporary policies as, in themselves, increasingly multifaceted, complex and composed of thick, interconnecting relations and heterogeneous actors. The practices and processes of policies assemble sets of heterogeneous actors including humans and an array of technologies such as templates, checklists and guidelines (Easthope & Mort, 2014). Easthope and Mort (2014) point to the many assumptions carried by such technologies, and Harrison and Mort (1998) figure policies as ‘technologies of legitimation’ which act to distribute relations of power and generate categories of difference (see also Caldwell, 1968; Jasanoff, 2005; Scott, 1998; Waterton & Wynne, 1996; Wynne, 2001, 2002).…”
Section: Policymentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed, ethnographic, policy-specific studies have characterised contemporary policies as, in themselves, increasingly multifaceted, complex and composed of thick, interconnecting relations and heterogeneous actors. The practices and processes of policies assemble sets of heterogeneous actors including humans and an array of technologies such as templates, checklists and guidelines (Easthope & Mort, 2014). Easthope and Mort (2014) point to the many assumptions carried by such technologies, and Harrison and Mort (1998) figure policies as ‘technologies of legitimation’ which act to distribute relations of power and generate categories of difference (see also Caldwell, 1968; Jasanoff, 2005; Scott, 1998; Waterton & Wynne, 1996; Wynne, 2001, 2002).…”
Section: Policymentioning
confidence: 99%
“…Since the Western financial crash of 2008, in particular, care governed through the public sector has been subject to punishing austerity measures and to audits (sometimes of care itself, see Singleton & Mee, this volume) that alienate those caring as well as those cared for. In more ambiguous, extreme and sometimes international situations the human impulse to care has come under intense pressure – for example in situations of war, disaster and immigration (Convery, Mort, Baxter, & Bailey, 2008; Easthope & Mort, 2014; Ticktin, 2011; Clark & Bettini, this volume). Relations and practices or ‘doings’ of care (Barad, 2007, 2102; Mol, 2002; Puig de la Bellacasa, 2011) within such difficult and traumatised situations have at times become distorted, almost unrecognisable as care.…”
Section: Carementioning
confidence: 99%
“…Social scientific research has shown over many years that disaster is not a thing or event, but a process -usually slower and longer than commonly perceived (Knowles, 2014), certainly messier and more complex than the traditional emergency planning cycle of mitigation, preparedness, response and recovery implies, and as critiqued by Easthope and Mort (2014). Our work, then, joins calls to question what counts as a disaster: when, how and for whom (with an emphasis on children and young people) a disaster comes into being.…”
Section: Children and Young People As A Cultural Groupmentioning
confidence: 99%
“…‘Flood apprentices’ gained prominence for positive effects on community engagement and resilience building (Whatmore and Landstrom, 2011). Easthope’s ethnographic study of community participation in, and transformation of, national recovery and resilience guidance in flooded Toll Bar, South Yorkshire demonstrated the power of local actors to mobilise their experience (Easthope and Mort, 2014). The longitudinal ‘recovery diaries’ produced by 44 adults in Hull following the 2007 severe flooding demonstrated a ‘flood recovery gap’ in that for many people the recovery process is more gruelling than the flood ‘itself’ (Medd et al., 2015).…”
Section: Introductionmentioning
confidence: 99%